Bladder Involvement in Behcet’s Disease - Alizadeh, Farshid; Khorrami, Mohammad Hatef; Izadpanahi, Mohammad Hossein; Nouri-Mahdavi, Kia; Mohammadi Sichani, Mehrdad (Urology Journal, 2012)
Purpose: To review different aspects of the bladder involvement in Behcet’s disease as a rare complication. Materials and Methods: We searched PubMed, Ovid, and Google Scholar for Behcet’s and neuro-Behcet’s disease and neurogenic and neuropathic bladder, bladder involvement, voiding dysfunction, and urologic manifestations. Fourteen full-texts and one abstract were retrieved. Results: Most involved patients are young to middle-aged men. Both bladder filling and emptying problems can be seen, with the storage symptoms being the most common finding. Sphincter function could be normal, dyssynergic, or deficient. The most common urodynamic finding is detrusor overactivity. In cystoscopic examination, ulcers or nodules due to vasculitis can be seen, which along with neurologic causes give rise to the voiding symptoms. The rate of cancers does not increase in Behcet’s disease. Surgery and chemotherapy are tolerated well. However, radiotherapy may be associated with increased complication rates. Conclusion: Treatment plan should be tailored according to the specific type of the bladder involvement. Periodic re-evaluation is required because of the changing nature of the bladder behavior.